Зміст і обсяг поняття “Міщанство” (етноісторичний підхід) - Кунцевська, О. (Народна творчість та етнографія, 2009)
The given article deals with an issue of low middle «class» definition on the example of Kiev bourgeois. The author stresses that maintenance and volume of this notion have changed in time. She also provides general definition for further analytical city culture researches.